2000
DOI: 10.1016/s0735-1097(00)00595-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of controlled breathing, mental activity and mental stress with or without verbalization on heart rate variability

Abstract: Simple mental and verbal activities markedly affect HRV through changes in respiratory frequency. This possibility should be taken into account when analyzing HRV without simultaneous acquisition and analysis of respiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
314
5
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 432 publications
(354 citation statements)
references
References 13 publications
30
314
5
5
Order By: Relevance
“…Immediately the resting, Systolic Blood Pressure (SBP) and Diastolic Blood Pressure (DBP) was also recorded. Subjects were then be asked to perform the serial subtraction task (a type of mental stress task) wherein the subject serially subtracts the number seven from a large number (eg 1024) and also vocalising the results of each step [14]. Lead II ECG and BP recordings were obtained during the mental stress task.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately the resting, Systolic Blood Pressure (SBP) and Diastolic Blood Pressure (DBP) was also recorded. Subjects were then be asked to perform the serial subtraction task (a type of mental stress task) wherein the subject serially subtracts the number seven from a large number (eg 1024) and also vocalising the results of each step [14]. Lead II ECG and BP recordings were obtained during the mental stress task.…”
Section: Discussionmentioning
confidence: 99%
“…A slower respiratory rate would give a slightly higher HF component (as an artifact) and could account for the non-significant tendency for a higher HF component in the women with PMS compared with controls. Investigators of HRV in subjects who are awake have attempted to minimize the influence of respiratory rate by controlling breathing rates, but controlled breathing can also impact HRV measures (39), and obviously cannot be done during sleep. We did not find any difference in HFfr between menstrual phases in either study group.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [30] have shown that this procedure, if properly performed, does not induce major modifications in the autonomic tone, yet allows correct analysis of HRV by removing artefact effects of irregular respiration into the low-frequency band [31]. Subsequently, participants were asked to take deep breaths at a fixed frequency of six breaths per minute for 1 min.…”
Section: Study Populationmentioning
confidence: 99%